2006
DOI: 10.1158/1078-0432.ccr-05-0964
|View full text |Cite
|
Sign up to set email alerts
|

Expression of KLF5 is a Prognostic Factor for Disease-Free Survival and Overall Survival in Patients with Breast Cancer

Abstract: Purpose: Kruppel-like factor (KLF5) is a cell growth mediator in various epithelial cells. Higher KLF5 increases cell growth rate and leads to transformed phenotypes. Because tumor cell proliferation is tightly associated with tumor progression, and consequently, with survival of cancer patients, we wanted to examine the prognostic value of KLF5 gene expression for patients with breast cancer. Experimental Design: The gene expression levels of KLF5, ER, PR, HER2, and MKI67 were quantified in the tumor tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 23 publications
5
92
0
Order By: Relevance
“…KLF5 has been reported to be an independent prognosis marker in breast cancer because patients with higher KLF5 mRNA expression have shorter survival than patients with lower KLF5 expression (Tong et al, 2006). This observation was further supported by independent microarray studies (Oncomine.org).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…KLF5 has been reported to be an independent prognosis marker in breast cancer because patients with higher KLF5 mRNA expression have shorter survival than patients with lower KLF5 expression (Tong et al, 2006). This observation was further supported by independent microarray studies (Oncomine.org).…”
Section: Discussionmentioning
confidence: 63%
“…Functionally, both genes promote cell transformation and angiogenesis (Czubayko et al, 1997;Shindo et al, 2002). Finally, both genes have been reported to be overexpressed in breast cancer (Kagan et al, 2003;Tong et al, 2006). However, whether KLF5 directly binds to the FGF-BP promoter, upregulates its transcription and functions through FGF-BP in breast cancer are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that high expression of KLF5 is also observed in breast cancer, we additionally compared KLF5 expression to MCF-7 breast cancer cells and found similar results in terms of a higher expression by pancreatic cancer cells (data not shown; refs. 6,19). Importantly, we found that phosphorylation of MEK did not strongly correlate with KLF5 levels, suggesting that the MEK pathway might not be the critical determinant for KLF5 up-regulation in pancreatic cancer cells (Fig.…”
Section: Expression Of Klf5 In Pancreatic Cancermentioning
confidence: 80%
“…This transcription factor is also known as an intestinal-enriched KrĆ¼ppel-like factor and is predominantly present in the proliferating crypt epithelial cells of the intestine (5). Nevertheless, controversy persists as to whether this transcription factor functions as a tumor suppressor or as an oncogene because clinical studies have shown that KLF5 overexpression is either associated with a poor prognosis in patients with breast cancer (6) or correlates with improved survival in patients with gastric cancer (7). Moreover, a recent experimental study showed that restoring KLF5 expression in prostate cancer cells reduces tumor growth in preclinical tumor models (8), and one study additionally suggested a metastasis-suppressive action of KLF5 in TE2 esophageal carcinoma cells (9).…”
Section: Introductionmentioning
confidence: 99%